2001
DOI: 10.1054/bjoc.2001.2156
|View full text |Cite
|
Sign up to set email alerts
|

ALA and ALA hexyl ester-induced porphyrin synthesis in chemically induced skin tumours: the role of different vehicles on improving photosensitization

Abstract: Exogenous administration of 5-aminolevulinic acid (ALA) is becoming widely used to enhance the endogenous synthesis of Protoporphyrin IX (PpIX) in photodynamic therapy. We analysed porphyrin formation in chemically induced squamous papillomas, after topical application of ALA and ALA hexyl ester (He-ALA) administered in different formulations, as well as the pattern of distribution in the internal organs, and the synthesis of porphyrins in distant tumoural and normal skins. A lotion formulation containing DMSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 19 publications
2
23
0
5
Order By: Relevance
“…Through fiber-optic detection of porphyrins, we have observed that after topical application, ALA induced rapid diffusion of porphyrins to other distant sites within the skin, but this was not observed for the ALA peptides. Such a phenomenon has been previously remarked upon by us, along with a higher confinement of porphyrin synthesis from He-ALA to the application site (51). In our previous studies, a similar amount of porphyrins from ALA was synthesized in distant papillomas when compared with ALA-applied papillomas, demonstrating that either ALA itself and/or the porphyrins formed by synthesis can be distributed throughout the vasculature and accumulate in distant tumors, and though it is likely that ALA is the molecule diffusing to distant sites, we cannot discount the contribution of hydrophilic precursors of PpIX such as uroporphyrin and coproporphyrin.…”
Section: Discussionsupporting
confidence: 58%
“…Through fiber-optic detection of porphyrins, we have observed that after topical application, ALA induced rapid diffusion of porphyrins to other distant sites within the skin, but this was not observed for the ALA peptides. Such a phenomenon has been previously remarked upon by us, along with a higher confinement of porphyrin synthesis from He-ALA to the application site (51). In our previous studies, a similar amount of porphyrins from ALA was synthesized in distant papillomas when compared with ALA-applied papillomas, demonstrating that either ALA itself and/or the porphyrins formed by synthesis can be distributed throughout the vasculature and accumulate in distant tumors, and though it is likely that ALA is the molecule diffusing to distant sites, we cannot discount the contribution of hydrophilic precursors of PpIX such as uroporphyrin and coproporphyrin.…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless they both are similar to oil-in-water emulsion where Gantrez may be considered as the oil component and the PVP as the water component. Oil-in-water emulsions are known to enhance lipophilic ALA hexylester localization in tumour whereas saline-DMSO-ethanol composition enhances amphiphilic 5-ALA (zwitterions) localization (28). In this study it was observed that PME in Gel-1 exhibited statistically significant selectivity at all time-points.…”
Section: Discussionmentioning
confidence: 57%
“…In conclusion, according to these results and those from Casas et al (2001b) when compared to ALA, only superficial skin lesions may be successfully treated with topical He-ALA PDT with the advantage of tumour selectivity; instead malignancies such as chest wall progression of breast cancer will probably fail this treatment. …”
Section: Discussionmentioning
confidence: 79%
“…However, in a previous work (Casas et al, 2001b) we have analysed porphyrin formation in chemically induced squamous papillomas, after topical application of ALA and He-ALA in cream and lotion formulations. Not only did we find porphyrin synthesis from ALA in these highly keratinised papillomas, but we also found porphyrin accumulation in internal organs, showing that the ALA-hexyl ester does reach the dermis in this tumour model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation